Boron trichloride purification with a KrF excimer laser - Hyer, R.C.; Hartford, A. Jr.; Atencio, J.H. (Los Alamos Scientific Laboratory, 1980)
Selective ultraviolet photolysis using a KrF excimer laser has been used to substantially reduce the phosgene impurity in a binary mixture of boron trichloride and phosgene. Infrared spectroscopic analysis of the sample before and after irradiation shows that it is possible to highly purify commercially available boron trichloride with this technique.